Real clinical practice of complicated Crohn’s disease treatment with ustekinumab: clinical case presentation - P. A. Makarchuk; E. Yu. Lomakina; E. A. Belousova; S. E. Dubrova (Медицинский совет, 2022)
Crohn’s disease (CD) is a severe immune-mediated disease with segmental transmural inflammation and ulcers in gastrointestinal tract most often in terminal ileum and colon. The disease is often associated with severe complications such as fistulas and strictures that require aggressive treatment or surgery. CD treatment remains the unresolved and one of the most serious problems in gastroenterology. Glucocorticosteroids (GCS) are the essential treatment options for many years but unfortunately the frequency of steroid resistance and steroid dependence are constantly increasing. In the cases of steroid refractory CD treatment options include biologics of different classes: tumour necrosis factor alfa - inhibitors (iTNF-α), α4β7 integrin inhibitor (vedolizumab), IL-12/23 inhibitor (ustekinumab). Any of these drugs can be used in bio-naïve CD patients, however secondary loss of response was noted for all biologics over time.In the cases of the first line treatment failure the problem of correct choice of the second and subsequent lines of biologics appears, since some biologics may show lower efficacy in the second line of treatment. Real clinical practice will allow us to make a more correct choice of next biologic. Ustekinumab, a human interleukin -12/23 monoclonal antibody is one of biologics that is highly effective in the first-line CD therapy and remains effective in the subsequent lines of treatment. We present a clinical case of complicated CD in young female with negative disease prognosis and loss of response to three iTNF-α. In this case the high efficacy of ustekinumab after multiple iTNF-α failure was demonstrated.